Analisis Margin Pemasaran Wortel Pada Kelompok Tani Marawis Di Kelurahan Rurukan Kecamatan Tomohon Timur - Meify C. Sumampow; Celcius Talumingan; Olvie L.S. Benu; Ellen G. Tangkere (Universitas Sam Ratulangi, 2013)
Sumampow Meify, Analysis of Carrot Marketing Margin Of Maramis Farmer’s Group At Rurukan village, East Tomohon Subdistrict, Chariman Under Guidance Of C. Talumingan As, And Benu. O.L.S., Ellen Tangkere As membersThe objective Of The research in to find out how much margin marketing and farmer share in marketing channels in urban MarawisRurukan. Data obtained by interview using the questionnaire as a tool in data collection. 20 respondents of farmer sampling, done in purposive sampling (intentional) while 3 respondents traders and retailers 3 respondents, done in Snowball sampling. Analysis of the data used is descriptive to portray the existing marketing channels and continue with the analysis of marketing margins and farmer share.Based on the results of research in urban Rurukan earned marketing channel model as follows:Farmers Collectic trader Retailer Trader ConsumerThe research result Indicated that margin at the level that is equal Rp.7.000 traders or 56.75%, margin is formed from the difference between the sales price of carrots at the collectors and the sale price of carrots at the farmer level. This is because traders bear the cost of labor, transportation and others. Profit earned by middlemen Rp. 2250 or 18.24%. Then the carrots for sale at retailers establish margin was Rp. 6583 or 53.37% margin was formed from the difference between the sales price and the selling price retailers carrots collector. Price carrots were sold to the final consumer is Rp. 12.333/kg.Based on farmers' marketing channel occurs. it can be concluded that the farmer share received by farmers was equal to 20.27%. This is due to non-2institution Due formed marketing in the marketing process carrots, wherein eachmarketing agencies to gain advantage in the marketing process plant carrots.This study shows that the marketing margin traders to retailers amountedto Rp 7.000, the marketing margin of retailers to consumers amounting to Rp6.583, so that the marketing margin from producers to consumers is equal to13.583. in marketing channels is part farmer farmers share the received was2027%. Therefore, it is need an effort to strengthen the bargaining position offarmers,to incraese the farmer’s share.